Dr. Somenath Dutta, Discoverer of Micro-RNA (MiRNA) Therapeutic to Prevent Harmful Zika Virus for Liver Cancer: A Scientometric Portrait - Dr. Susanta Koley; Sutapa Goswami (International Journal of Virus Studies, 2025)
Dr. Somenath Dutta allies Rahul is a global recognized scientist for his outstanding recent discovery of “miRNA therapeutics for the Zika virus” at the age of 26 years, which can be cured Liver Cancer and allied health problems due to Zika virus disease. This study covers his 12 publications in variety of forms including 07 journal articles (59%), 03 conference papers (25%), 01 dissertation, and 01-chapter paper during 2019-2024. All are published within a short time span of 6 years of his active productive age, with an average 2 papers per year, that is a healthy trend. His discovery at the age 26 has lifted him to the first milestone of his success. His first paper appeared in the year 2019 when he was 21 years old. Still now, he contributed different papers in collaboration with 45 (individually 31) co-authors; but he appeared as first author in maximum number of papers i.e. 07, and are published in 07 national and international journals. Journal of Global Oncology (On behalf of the American Society of Clinical Oncology) is more remarkable as after getting global recognition, his discovery was published in this USA based journal. His publications are emanated from India, USA, UK, Switzerland, and Bulgaria. Somnath De is his closet collaborator who has published 6 papers in association with the scientist, with an average of 2 papers per year. Over all corelation co-efficient is 1. Lotka’s Law does not satisfy but the data set of this study validates Bradford’s Law.
Keywords: Busan-South Korea; Liver Cancer; Mosquito-borne transmission; Pusan National University; Somenath Dutta; miRNA therapeutics; scientometric analysis; zika virus